Best Kept Secret Book 3 - Archer, Jeffrey 1940- (New York : St. Martins Press, 2013)
Embarking on a shared family life, Harry, Emma, Sebastian, and Jessica find their happiness challenged by Emmas brothers engagement to a fortune-seeker, Sebastians hedonist pursuits, and a grudge-bearing enemy from the past who would destroy their careers.
Keywords: Families -- England; History -- 20th century; Fiction; Family secrets -- Fiction